Pemaksaan Zakat oleh Pemerintah dalam Perspektif Hukum Islam dan Penerapannya di Indonesia - Aqbar, Khaerul; Herman, Sulkifli; Asri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to examine how the application of zakat at the time of the Prophet. and khulafaurasyidin as well as examining how the zakat enforcement system in Indonesia and its application from the perspective of Islamic law. In this study, the authors use a type of library research (library research) whose data sources are obtained from written sources, including books, laws, fiqh books, journals, the internet, and other scientific papers related to the object under study, by using Sharia normative theological approach, juridical approach, and sociological approach. The research results found by researchers are as follows; First, zakat is one of the pillars in supporting the economy of Muslims to overcome economic, social, educational, and health disparities in the country of Indonesia. second; The imposition of zakat in Indonesia can be done by revising the contents of law number 23 of 2011, which is to reduce tax for muzakki on zakat that has been fulfilled. third; the government can impose zakat on the Indonesian Muslim community as long as it can manage zakat by the Sharia without any element of cheating in it. fourth; zakat can be enforced in Indonesia if it can strengthen the role of BAZNAS, LAZ, and BAZ nationally by Article 23 of 2011 Law. Fifth; the imposition and management of zakat at the time of the Prophet and khulafaurrasyidin is something that should be emulated because history has proven its success in managing zakat. sixth; muzakki may distribute their zakat directly to mustahik without going through institutions either from the government or institutions under the protection of the government. seventh; according to the perspective of the Islamic law that every leader who manages the affairs of the Muslims is obliged to take care of his affairs by the provisions of the Shari'a. Eighth; in surah al-Taubah / 9 verse 103 the leaders have been instructed to take zakat from Muslims by applicable regulations.